Influence of facing panel rigidity on performance of reinforced soil retaining walls: a numerical study - Castorina Silva Vieira (2008)
Geosynthetic-reinforced soil retaining walls are typically designed on considerations of limit equilibrium. These methods disregard the effects due to foundation condition, reinforcement stiffness, facing type and other factors. Deformations of the wall are generally not explicitly considered in design. In this work, the two-dimensional finite difference Fast Lagrangian Analysis of Continua (FLAC) program was used to carry out parametric analyses. The numerical study was carried out to analyse the influence of facing panel rigidity and wall height on horizontal deformations and reinforcement tensile loads of geosynthetic reinforced soil retaining walls with continuous facing panel. For the same facing panel bending stiffness different values of wall height are investigated. The numerical analyses showed that the pattern of normalized horizontal displacements and normalized reinforcement tensile loads, for structures with the same facing panel rigidity and reinforcement stiffness factor, are distinct. However, if the facing panel bending stiffness for distinct wall heights obeys to a presented equation, good agreements related to normalized displacements and normalized reinforcement loads are achieved.